A New Approach To Groundwater Monitoring Well Network Design For Heap Leach Pads Using The Monitoring Well Efficiency Model (Memo) - C. Einberger (Society for Mining, Metallurgy & Exploration, 1993)
Groundwater Monitoring is typically required by regulatory agencies at potentially hazardous landfills or surface impoundments. Agencies have often required an arbitrary number of wells with limited evaluation of the effectiveness of the network to detect a leak. A Monitoring Efficiency Model (MEMO) has been developed to improve the design and cost effectiveness of monitoring well networks. MEMO 15 an analytical model that simulates the migration of hypothetical contaminant plumes from a site and quantifies the efficiency of alternative well network designs in detecting the plumes. The computed monitoring efficiency provides a quantitative measure of the well network adequacy based on hydrogeologic considerations. The model was recently used to design the groundwater monitoring well network for a heap leach pad at the proposed Beartrack Project.